A Comparative In Vitro Digestion Study of Three Lipid Delivery Systems for Arachidonic and Docosahexaenoic Acids Intended to Be Used for Preterm Infants - Blanca Pardo de Donlebún; Assamae Chabni; Celia Bañares; Carlos F. Torres (Molecules)
It is well stablished that docosahexaenoic (DHA) and arachidonic (ARA) acids fulfill relevant biological activities, especially in newborns. However, oils containing these fatty acids are not always optimally digestible. To address this, various formulation strategies and lipid delivery systems have been developed. This study compares the following three formulations in an in vitro digestion model to assess bioaccessibility: Enfamil® DHA & ARA (Mead Johnson & Company), an emulsion of FormulaidTM, AquaCelle®, and pasteurized donated human milk, and a previously characterized enzymatic glycerolysis product (GP) of ARA oil and microalgae oil in a 2:1 (w:w) ratio. To evaluate digestibility, parameters such as the percentage of oily phase (OP), micellar phase (MP), free fatty acids, and monoacylglycerols in the digestion product (DP) were considered. Additionally, diacylglycerol content in the MP can be used as an indirect marker of the emulsification capacity of the DP, and consequently, as an indicator of bioaccessibility. The GP demonstrated the highest bioaccessibility, with a DP containing more than 80% MP (<14% OP), rich in free fatty acids (60%) and monoacylglycerols (17%). Furthermore, more than 40% of total diacylglycerols were present in MP, highlighting GPs’ potential as a superior delivery system for DHA and ARA in preterm infant formulations.